The implementation of school-literacy-movement: Integrating scientific literacy, characters, and HOTS in science learning - Suryawati, Evi; Suzanti, Fitra; Suwondo, Suwondo; Yustina, Yustina (University of Muhammadiyah Malang, 2018)
This study aimed to examine the implementation of the School Literacy Movement (SLM) by observing its impacts toward the scientific literacy, characters, and HOTS of Grade VII Junior High School (JHS) students in Pekanbaru within the context of K-13. The survey was conducted with 45 natural science teachers on the basis that they have integrated K-13 into their teaching and learning. The data of SLM implementation was obtained from the teacher by means of questionnaires and observation which was conducted in science classes in three JHS in pollution and global warming topics. The results showed that 49.13% of activities were successfully implemented by SLM. The results showed that studentsâ scientific literacy in the three schools were 69.5%, 76.3%, and 75.2%. Meanwhile, the character values have reached 80.6%, 76.4%, 72.9%, and studentsâ HOTS values were 73.0%, 72.5%, and 73.3%. Based on the survey, it can be concluded that although the school has pioneered SLM, the strengthening of scientific literacy, characters, and HOTS has not been executed by all teachers who implement K-13 due to various obstacles need new policies to assess the execution of the SLM program by the local education department.